Beyond Recanalization: A Mechanistic and Procedural Framework for Adjunct Pharmacologic Therapy During Mechanical Thrombectomy - Saniyah Shaikh; Touleen T. Raslan; Affaf Tanweer; Zainab Nasir; Hibba Siraj; Thaabit Raziq; Umaima Shoukat; Volodymyr Mavrych; Olena Bolgova; Ahmed Yaqinuddin (Journal of Clinical Medicine, 2026)
Endovascular thrombectomy [EVT] has revolutionized acute ischemic stroke care by restoring macrovascular reperfusion in large vessel occlusion; however, a persistent “reperfusion–outcome gap” remains, leaving nearly half of successfully recanalized patients without functional independence. This review aims to bridge this translational gap by establishing a mechanistic and procedural framework for adjunctive pharmacotherapy designed to target the microvascular, thromboinflammatory, and reperfusion-related injuries left unaddressed by purely mechanical models. Synthesis of recent literature reveals that futile recanalization is driven by three distinct anatomical and biological bottlenecks: distal microembolization, microcirculatory no-reflow, and ischemia–reperfusion injury. Furthermore, the inconsistency of clinical trial results reflects a critical precision deficit, including dilution of treatment effects across heterogeneous reperfusion grades, inadequate stroke etiology stratification, delayed pharmacologic intervention relative to evolving microvascular injury, and reliance on functional endpoints that inadequately capture tissue-level reperfusion. To address these limitations, this review outlines a tri-axial clinical decision framework integrating reperfusion status, stroke etiology and hemorrhagic risk, which maps specific patient phenotypes, such as incomplete macrovascular reperfusion or underlying intracranial atherosclerotic disease, to targeted pharmacologic strategies including microcatheter-directed intra-arterial thrombolytics and glycoprotein IIb/IIIa inhibitors. The review further argues that future progress will require imaging-guided identification of residual hypoperfusion, mechanistically enriched patient enrolment, and incorporation of biological and tissue-level reperfusion endpoints alongside conventional functional outcomes. Ultimately, closing the reperfusion–outcome gap will require moving beyond empirical, universal drug administration toward a precision, pharmacologically augmented EVT paradigm that aligns adjunctive therapy with mechanism-specific procedural phenotypes and prioritizes true tissue-level recovery over angiographic success alone.